2018
DOI: 10.1007/s12310-018-9264-5
|View full text |Cite
|
Sign up to set email alerts
|

What is in It for Them? Understanding the Impact of a ‘Support, Appreciate, Listen Team’ (SALT)-Based Suicide Prevention Peer Education Program on Peer Educators

Abstract: Youth suicide is a public health problem in India, and young people in school, particularly adolescents, experience heavy psychological burden. Prevention programs, involving peer educators (PEs), have proved useful strategies to address this problem, but their impact on the PEs is less understood, particularly in India. This qualitative study aims to explore the changes observed in PE students who were involved in a ‘mindfulness’ and ‘Support-Appreciate-Listen–Team’ (SALT)-based peer education program to addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 65 publications
0
11
0
2
Order By: Relevance
“…Research has shown that students in distress regard their peers as their first line of contact in help‐seeking, 12 and that positive peer relationships function as a protective factor against stress 13 . Noting the importance of peers in protecting students' mental health, schools have begun to adopt the student‐led approach in programs, which have effectively heightened students' readiness to support their peers, 14 increased students' sense of connection and belonging to their school, 15 and improved peer leaders' emotional intelligence, 16 all of which reaffirm the value of empowering students to promote their peers' mental health.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that students in distress regard their peers as their first line of contact in help‐seeking, 12 and that positive peer relationships function as a protective factor against stress 13 . Noting the importance of peers in protecting students' mental health, schools have begun to adopt the student‐led approach in programs, which have effectively heightened students' readiness to support their peers, 14 increased students' sense of connection and belonging to their school, 15 and improved peer leaders' emotional intelligence, 16 all of which reaffirm the value of empowering students to promote their peers' mental health.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Secondly, students' lack of interest and perceived stigma toward mental health highlighted a need to promote and destigmatize mental health in ways that are more appealing to students. Other difficulties included difficulty in making time for wellbeing‐promoting activities 16 . In short, both personal and organizational factors have challenged the success of introducing peer‐led mental health promotion into schools.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Health care professional must understand about the reason of youth needs and willingness to engage in capacity strengthening (Mukherjee, 2015). Youth participation is not only limited to their social support such as being peer educator for depression and bullying problem (Yin et al, 2017;Zachariah et al, 2018), but youth must participate to take care or maintain their family health behaviour too. When health care professional could not see this opportunity and youth capacity, youth can act passive or felt being excluded.…”
Section: Youth and Capacity Strengtheningmentioning
confidence: 99%
“…The results indicate that that the mindfulness and Support, Appreciate, Listen, Team (SALT) using Peer Educators (PE) have enhanced the PEs broad emotional intelligence and PEs expressed increased ownership of life, taking actionand seeking support when needed. Research studies also suggest that future research should be carried out in developing nations to understand the knowledge regarding suicides especially in the adolescent age group (5) . WHO further emphasizes that India develop a comprehensive suicide prevention plan and integrate it with the mental health act to contain the growing threat of adolescent suicides.…”
Section: Introductionmentioning
confidence: 99%